2021
DOI: 10.3390/en14113310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and CFD Investigation on the Application for Aerogel Insulation in Buildings

Abstract: Reducing building energy consumption is a significant challenge and is one of the most important research areas worldwide. Insulation will help to keep the building’s desired temperature by reducing the heat flow. Additionally, proper insulation can provide an extended period of comfort, leading to reduced building energy requirements. Encapsulated air is the major aspect of most thermal insulation materials. Low thermal conductivity is a good characteristic of thermal insulation materials. Aerogel has low the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…This means that insulation materials need to be selected based on climatic conditions [57,58]. As such, research depicts that the application of a small thickness of aerogel-based rendering on the exterior surface of insulated or non-insulated walls significantly reduces heat losses and removes the risk of moisture, thereby improving the energy efficiency of the buildings [59,60].…”
Section: Insulation Materialsmentioning
confidence: 99%
“…This means that insulation materials need to be selected based on climatic conditions [57,58]. As such, research depicts that the application of a small thickness of aerogel-based rendering on the exterior surface of insulated or non-insulated walls significantly reduces heat losses and removes the risk of moisture, thereby improving the energy efficiency of the buildings [59,60].…”
Section: Insulation Materialsmentioning
confidence: 99%
“…Thermal comfort inside an office equipped with an HVAC system was evaluated with the use of the finite volume method in [28]. The application of aerogel in building isolation was investigated by means of CFD simulations and experimental research in [29].…”
Section: Heat Transfer Simulationsmentioning
confidence: 99%
“…They deposited translucent aerogel glazing systems in the walls and windows of different buildings for better insulation performance. The results demonstrated that the deposition of aerogels in the wall and window insulation and glazing systems has significant potential to reduce energy consumption and cost of buildings [ 90 ]. Qi et al reported the tribology behavior of silica aerogels reinforced with polybutylene terephthalate for a deep-sea environment.…”
Section: Applications Of Aerogelsmentioning
confidence: 99%